Association of Medicaid expansion with health insurance coverage by marital status and sex. - Jim P Stimpson; Jessie Kemmick Pintor; Fernando A Wilson (PLoS ONE, 2019)
OBJECTIVE:To determine the association of Medicaid expansion with health insurance coverage by marital status and sex. METHODS:A population-based, quasi-experimental policy analysis was undertaken of the implementation of the Patient Protection and Affordable Care Act's (ACA) Medicaid expansion provision on or after January 1, 2014. The 2010-16 American Community Survey provided data on 3,874,432 Medicaid-eligible adults aged 19-64 with incomes up to 138% of the federal poverty level. The outcome measures were no health insurance coverage and Medicaid coverage. The predictor variables were marital status and sex, with controls for family size, poverty status, race/ethnicity, education, employment status, immigration status, and metropolitan residence. RESULTS:In 2016, the uninsured rate for married men and women in a Medicaid expansion state was 21.2% and 17.1%, respectively, compared to 37.4% for married men and 35.8% for married women in a non-expansion state. The Medicaid coverage rate grew between 14.8% to 19.3% in Medicaid expansion states, which contrasts with less than a 5% growth in non-expansion states. Triple differences analysis suggests that, for women of all age groups, Medicaid expansion resulted in a 1.6 percentage point lower uninsured rate for married women compared to unmarried women. For men, there was not a statistically significant difference in the uninsured rate for married compared to unmarried men. For women of all age groups, there was a 2.6 percentage point higher Medicaid coverage rate for married compared to unmarried women. For men, there was a 1.8 percentage point higher Medicaid coverage rate for married compared to unmarried men. CONCLUSION:Medicaid expansion under the ACA differentially lowered uninsurance and improved Medicaid coverage for married persons, especially married women, more than unmarried persons.